A NEW REFUTATION OF THE CLASSICAL CONCEPT OF TIME IN QUANTUM RELATIVITY (Empirical Study on Listed Company) - Pujiastuti Pujiastuti; Sugiarti Sugiarti; Yunus Hardjito (Jurnal AKTUAL, 2021)
The research objective was to determine (1) the influence of competency on audit quality (2) the influence of independence on audit quality and (3) the effect of professionalism on audit quality in public accounting firms in Surakarta and Yogyakarta. The population of this study is auditors who work on KAP in Surakarta and Yogyakarta who are registered in IAI in 2019. The sampling technique uses Convenience sampling. This study uses a statistical package for social science (IBM SPSS) version 21 for windows as an analysis tool. The results of this study indicate (1) Competence influences Audit Quality (2) Independence influences Audit Quality and (3) Professionalism influences Audit Quality.Keywords: Competence, Independence, Professionalism and Audit Quality.